A Comparative Study of Negative Pressure Dressing with and without Silver Alginate to Promote Faster Wound Healing in Chronic Wounds - Ali, Mehak; Ali, Hyder; Akhlaq, Faisal; Adil, Faraz; Naseem, Aiman; Ali, Urooj (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the effectiveness of negative pressure dressing with silver alginate hydro-fibre dressings in managing chronic wounds compared to negative pressure dressing without silver alginate hydro-fibre dressings. Study Design: Cross-sectional analytical study. Place and Duration of the Study: Department of Plastic and Reconstructive Surgery at Dr Ruth K.M. Pfau Civil Hospital Karachi, from Jan to Jul 2021. Methodology: All patients above 18 years of age of either gender presented with more than six weeks of wound duration, hemoglobin levels more than 10 g/dl, platelet count above 150 x 10E9/L, and size of the wound more than 10*10cm were consecutively enrolled. Negative pressure dressings with and without hydro-fibre dressings were applied. A team of plastic surgeons monitored the wound site to assess granulation tissue by noting the size of the wound and pain severity. The outcome was assessed at four weeks. Results: Of 62 patients, the median age was 43 (32.5-56.7) years. There were 37 (59.67%) males and 25 (40.32%) females. The outcome assessment at four weeks showed that overall pain was observed in 34 (54.83%) patients. Pain severity (p-value <0.001) and low granulation score (p-value 0.025) were found significantly higher in patients who received negative pressure dressing without silver alginate as compared to the patients who received negative pressure dressing with silver alginate. A significant median difference in granulation days was observed between groups (p-value <0.001). Conclusion: Combining negative pressure dressings with silver alginate dressing has positive effect on the chronic wound compared to using negative pressure dressings alone.